If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24x + -94 = x + -10 Reorder the terms: -94 + 24x = x + -10 Reorder the terms: -94 + 24x = -10 + x Solving -94 + 24x = -10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -94 + 24x + -1x = -10 + x + -1x Combine like terms: 24x + -1x = 23x -94 + 23x = -10 + x + -1x Combine like terms: x + -1x = 0 -94 + 23x = -10 + 0 -94 + 23x = -10 Add '94' to each side of the equation. -94 + 94 + 23x = -10 + 94 Combine like terms: -94 + 94 = 0 0 + 23x = -10 + 94 23x = -10 + 94 Combine like terms: -10 + 94 = 84 23x = 84 Divide each side by '23'. x = 3.652173913 Simplifying x = 3.652173913
| -9r+10=8+3r | | 10-5(9n-9)=10 | | 4x^2-x-29=0 | | 5/20=9/x | | 18a^2-48a+32=0 | | x+-5=2x+1 | | -3(2x+7)=-6x-21 | | 1.5(m-3)=12 | | 2x+y=3.5 | | 3secx-5=-8 | | 3(2p+1)=7(-p)-6 | | x^2-4x^1+3=0 | | 3.4c-17=68 | | 9y=-x+9 | | -28(z-73)=z+6 | | 13x+5y=17 | | 6x+4x+4+8=5x+3+4x | | 4a^2+19a+12=0 | | (7.1)1.9= | | -2y+3=-9 | | -2y+3=-8 | | 5g+4(-8+5g)=1-g | | 74y-4884=y+(-72) | | 74y-4884=y+(-74) | | A-10=34 | | 16x-1.86x^2=0 | | (3x^2-5x)-(x^2+4x+3)= | | y=20+5x | | A=2400+144t | | 2(6z+1)-6=92 | | 7/8=y/56 | | 1.5y=1.25 |